2013
DOI: 10.1242/jeb.095398
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous changes in the swimming direction of sperm in the gastropodStrombus luhuanus

Abstract: The sperm of the gastropod Strombus luhuanus show dimorphism. The eusperm have a nucleus and fertilize the egg, whereas the other type of sperm, parasperm, are anucleate and are thought to assist fertilization. Here we report the autonomous changes in the swimming pattern of S. luhuanus eusperm. In artificial seawater, the eusperm collected from S. luhuanus sperm ducts formed sperm bundles and initially swam backward with asymmetric flagellar waveforms to detach from the bundles. One hour later, the sperm bega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In animals, calcium usually inhibits flagellar or ciliary motility: calcium induces ciliary arrest in mussel gill cilia [101][102][103], in ascidian gill slits [104] and in embryonic epidermal cilia of sea urchins [105]. In sperm cells of ascidians [106], sea urchins [107,108], siphonophores [109] and snails [110], calcium bursts increase the asymmetry of flagellar beating and the swimming curvature, which serves to change direction during chemotaxis [111]; in Ciona sperm cells, the calcium sensor has been shown to be calaxin, a protein that directly inhibits outer-arm dyneins, thus triggering beating asymmetry [112]-showing that the response of sperm flagellar beating to calcium is inhibitory at the molecular level. Exceptions are known in vertebrates, such as the cilia of the vertebrate foregut (mammalian airways and frog oesophagus [98,113]) or the flagellum of mammalian spermatozoa [114], which respond to calcium by increasing beating frequency.…”
Section: (D) the Control Of Flagellar Beating By Calciummentioning
confidence: 99%
“…In animals, calcium usually inhibits flagellar or ciliary motility: calcium induces ciliary arrest in mussel gill cilia [101][102][103], in ascidian gill slits [104] and in embryonic epidermal cilia of sea urchins [105]. In sperm cells of ascidians [106], sea urchins [107,108], siphonophores [109] and snails [110], calcium bursts increase the asymmetry of flagellar beating and the swimming curvature, which serves to change direction during chemotaxis [111]; in Ciona sperm cells, the calcium sensor has been shown to be calaxin, a protein that directly inhibits outer-arm dyneins, thus triggering beating asymmetry [112]-showing that the response of sperm flagellar beating to calcium is inhibitory at the molecular level. Exceptions are known in vertebrates, such as the cilia of the vertebrate foregut (mammalian airways and frog oesophagus [98,113]) or the flagellum of mammalian spermatozoa [114], which respond to calcium by increasing beating frequency.…”
Section: (D) the Control Of Flagellar Beating By Calciummentioning
confidence: 99%
“…We previously reported that eusperm change motility in seawater autonomously, including backward asymmetric movement for detachment from the sperm bundle, circular and straight forward movement, and spontaneous backward swimming with symmetric flagellar waveforms ( Shiba et al, 2014 ). As Nishiwaki (1964) briefly mentioned, the Strombus parasperm also exhibited backward swimming.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm in some insects and snails reverse the direction of bend propagation in a Ca 2+ -dependent manner [ 26 - 30 ]. For example, in the sperm of the gastropod Strombus luhuanus , the reversal of bend propagation appears to be involved in sperm release from the sperm storage site in the female genital tract [ 30 ].…”
Section: Reviewmentioning
confidence: 99%